Re-directing developers: New models of rental housing development to re-shape the post-apartheid city?. (March 2020) - Todes, Alison; Robinson, Jennifer
The role of developers in shaping the built environment has attracted considerable critical attention, often focussing on the overbearing role of powerful, globalised actors in urban development. But there is also evidence that regulatory pathways shape outcomes. Through the case of a large-scale initiative in Johannesburg, South Africa, the "Corridors of Freedom", we consider whether there is potential for developmental benefit to be gained from redirecting developer interest to create new kinds of built form. Linked to investment in a bus rapid transit system and agile bureaucracy, a model of closely managed low-income rental housing is emerging, although there is evidence of some displacement of the poorest from more informal housing. The study suggests the importance of reassessing the political complexion and potential of state–developer co-operation in urban development, and of looking more closely at the diversity of developers as well as the array of forms of finance mobilised for urban development beyond financialisation.